IMPROVEMENT OF THE MARKETING COMPLEX OF THE INDUSTRIAL ENTERPRISE - MOROZ, OLENA; LATYSHEV, KOSTIANTYN; ZBYRANNYK, OKSANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
This article considers the issues on improvement of marketing complex of industrial enterprise, with the purpose of stabilization of its activity and strengthening of competitive positions. It is proposed to improve the activities of industrial enterprises on the basis of the formation of measures that will ensure the current support of domestic enterprises in difficult economic conditions. One of the ways of improving the performance of the company is to change the model "4P" into a model of marketing complex "5P" and use personnel ("Personal") as one of the tools. On the basis of the conducted research the influence of external environment factors was evaluated on the basis of the model of the marketing complex "4P". As a result, it was found that the surveyed company has low competitive advantages, but these competitive advantages may not be valid without preservation of highly qualified personnel, because of the instability of the activities of the company, constant differences in production, simple, reduction of workers or voluntary migration of manpower and as a result of the loss of highly qualified workers and the position of the leader in the field of machine building. The evolution of the marketing complex depending on the influence of factors of the marketing environment is examined. The application of the marketing complex not only contributes to satisfaction of needs of potential organizations in the framework of target markets, but also allows maximizing the efficiency of industrial enterprises' activity. Practical relevance of the research carried out in the article lies in the fact that using recommendations and directions of upgrading the marketing complex of industrial enterprise will ensure stabilization of its activity on the market due to the influence of regressive external factors.
Keywords: marketing complex; industrial enterprise; environment